2022
DOI: 10.18196/mb.v13i2.12888
|View full text |Cite
|
Sign up to set email alerts
|

Corporate Social Responsibility's (CSR) Impact on Financial Performance: Moderating Effects of Earnings Management and Leverage

Abstract: Research aims: This research attempts to test the impact of CSR on financial performance, with earnings management and leverage acting as moderating factors.Design/Methodology/Approach: The manufacturing companies listed on the Indonesia Stock Exchange (IDX) from 2015 to 2019 served as the study object. Purposive sampling was utilized in sample selection, yielding 228 samples. Multiple linear regression and moderated regression analysis were the analytical techniques used in this study, with the EViews 10 prog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
6
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 17 publications
1
6
0
1
Order By: Relevance
“…However, the relationship between the investment opportunity set and debt policy cannot be proven in this study (Ainul et al, 2023). Second, "Corporate Social Responsibility's (CSR) Impact on Financial Performance: Moderating Effects of Earnings Management and Leverage" (Rita et al, 2022) This research attempts to test the impact of CSR on financial performance, with earnings management and leverage acting as moderating factors. The analysis results indicated that CSR had no significant effect on financial performance; earnings management could not The rest of this paper elaborates upon the related literature.…”
Section: Sinurat Ilham Sinta and Ahmadmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the relationship between the investment opportunity set and debt policy cannot be proven in this study (Ainul et al, 2023). Second, "Corporate Social Responsibility's (CSR) Impact on Financial Performance: Moderating Effects of Earnings Management and Leverage" (Rita et al, 2022) This research attempts to test the impact of CSR on financial performance, with earnings management and leverage acting as moderating factors. The analysis results indicated that CSR had no significant effect on financial performance; earnings management could not The rest of this paper elaborates upon the related literature.…”
Section: Sinurat Ilham Sinta and Ahmadmentioning
confidence: 99%
“…The independent variable used is limited. " (Rita et al, 2022) ROE was the only indicator used to measure financial performance. Information about the company's CSR disclosure was only available from the annual report, and not all the disclosure's components were included.…”
Section: Sinurat Ilham Sinta and Ahmadmentioning
confidence: 99%
“…Selain itu, kewajiban yang digariskan dalam UU No. 40 tahun 2007 menekankan pentingnya penerapan CSR di berbagai industri, termasuk yang terkait dengan sumber daya alam, yang telah berkontribusi positif dalam mendorong pembangunan berkelanjutan di Indonesia (Kusumawati et al, 2022). Selain itu, penerapan CSR yang diwajibkan juga telah memainkan peran penting dalam mengurangi kemiskinan dan ketidaksetaraan.…”
Section: Bentuk Pelaksanaan Csr Menurut Undang-undang Perseroan Terba...unclassified
“…Based on previous research, CSR can have positive or negative effects on profitability that need further analysis. Meanwhile, some previous studies found the moderating role of leverage on the CSR effect on the profitability of non-bank firms (Kusumawati, Asyilah, & Bukhori, 2022;Rosiana & Akhmadi, 2023). Since banks as intermediaries have different types of leverage than non-bank firms, this research analyzes the influence of CSR with leverage as a moderating variable on the profitability of listed banks in Indonesia.…”
mentioning
confidence: 97%